UltraPulse Carbon Dioxide Laser Plus Methyl Aminolevulinate-Photodynamic Therapy for the Treatment of Penile Cancer - Santo Raffaele Mercuri; Giovanni Paolino; Pina Brianti; Matteo Riccardo Di Nicola; Alberto Martini; Andrea Necchi; Francesco Montorsi (Karger Publishers, 2022)
The treatment of early-stage penile carcinoma is usually represented by wide excision or partial penectomy with or without inguinal lymph node dissection. However, laser ablation of the tumor may have a prominent role as an organ-sparing approach. In this regard, the combination of UltraPulse CO2 laser and photodynamic therapy (PDT) may be a valid option, especially when surgery is not feasible or refused. UltraPulse CO2 laser allows for the formation of gentle cutaneous abrasion that destroys the malignant tissue and, at the same time, improving the uptake of methyl aminolevulinate and amplifying the photochemical reaction of PDT in the tumor and surrounding tissue.